2018
DOI: 10.2503/hortj.okd-135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 1-MCP and Pre-harvest Fruit Bagging Treatments on Cold Storability of the Red-fleshed Apple ‘Kurenainoyume’

Abstract: The evaluation of storability for the type 2 red-fleshed apple 'Kurenainoyume' is essential to expand its consumption for table and processing use, as the cultivation area of this cultivar has extended year by year. There is also little available information whether cold storage affects the skin and flesh coloration of 'Kurenainoyume' (type 2 apples). In the present study, we evaluated the effect of 1-methylcyclopropene (1-MCP) treatment on the storability of bagged and non-bagged fruit for respective table an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…J. Preview fruit showed longer storage periods compared with nonbagging (Matsumoto et al, 2018a). 'Kurenainoyume' also has potential for additional processing due to the characteristic red flesh coloration.…”
Section: Discussionmentioning
confidence: 99%
“…J. Preview fruit showed longer storage periods compared with nonbagging (Matsumoto et al, 2018a). 'Kurenainoyume' also has potential for additional processing due to the characteristic red flesh coloration.…”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, the conclusion is the opportunity to realize the bagging of apples with materials that allow the passage of a substantial part of light radiation to maintain unaltered the color of red apples [86] and to avoid the blush of the skin in acyan apples [47,81]. Alternatively, bags must be removed a few weeks before harvest to avoid the red color reduction in cyan apples [57] (Table 2). increase in anthocyanin content after bag removal, increased expression of genes involved in light signal perception and transduction [81] "Qinguan" (deep-red cultivar), "Cripps Pink" (pale-red cultivar), and "Golden Delicious" (non-red cultivar) red/pink pigmentation after bag removal, more intense in "Granny Smith" [85] "Idared" 40 d after full bloom 1-3 layers of black hail net small increase in mechanical properties Increase in russet susceptibility [86] "Fuji Raku Raku" 60-75 d after full bloom double layer paper (outer grey, inner red) lower internal browning with more rotting, lower phenolic content [87] In pears the evolution of external coloration following bagging is similar to that of apple fruits, as summarized in Table 3; in fact, it was demonstrated that anthocyanin accumulates rapidly if the Red Chinese sand pear (P. pyrifolia) fruits are subjected to light within 10 days from bag removal [48].…”
Section: Bagging and The Color Of Fruitsmentioning
confidence: 99%
“…Bagging technique leads to the production of more attractive fruits due to fewer blemishes and visible marks [ 9 ], particularly in apple [ 47 , 49 , 56 , 57 ], pear [ 12 , 58 , 59 , 60 , 61 ], peach fruits [ 10 , 62 ], pomegranate [ 41 ], mango [ 21 , 22 , 23 , 24 , 25 ], carambola [ 27 ], guava [ 14 , 28 ], litchi [ 29 , 30 ], loquat [ 31 , 32 ], persimmon [ 34 , 35 ] and yuzu [ 36 ]. In addition, post-harvest losses are significantly reduced for mango [ 26 ].…”
Section: The Role Of Bagging On Fruit Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The microclimate exhibited a positive influence on the structure of apple peels [20] and reduced the rotting in longan [19] and date palm [21], as well as fruit sunburn and cracking in pomegranate [22,23]. The bagging technique led to the production of more attractive fruits due to fewer blemishes and visible marks [13], particularly in apple [24][25][26][27], pear [17,[28][29][30][31], peach fruits [11], mango [32][33][34][35][36], carambola [37], guava [38], litchi [10,39], loquat [8], and persimmon [40,41].…”
Section: Discussionmentioning
confidence: 99%